Avaliação da qualidade na prestação de serviços em uma fábrica de tintas - Nogueira, Auanna Stephany (Universidade Federal Rural do Semi-Árido, 2019)
The need for population mobility over time, the imposition to arrive faster and faster at their destinations, allowed a gradual increase of vehicles on the streets. As a result came the increase in vehicle production demand, followed by the increase in maintenance activities. Among these activities is automotive repainting.The objective of this paper was to analyze the level of quality of services provided by an automotive paint manufacturer, applying the Servqual research instrument, so that it was possible to identify through the gaps and quality dimensions which services deserve to be improved within the company. company. Theoretical concepts related to the automotive paint market, customers and service quality were addressed. The research was conducted in the field of the company and together the analysis of the data obtained to obtain the final results of the study was performed. A questionnaire based on the aforementioned instrument was adapted and the method developed by US marketing researchers Parasuraman, Zeithaml and Berry was used. For data analysis, Cronbach's alpha descriptive statistics were used, followed by the calculation of gaps and quartiles. Analyzing the performance of the company, it was possible to observe through the quality gaps that the customers after the service ended satisfied with expectations met for safety dimension, for the tangibility and empathy dimensions the company had a reasonable evaluation according to the customer feedback and a negative result. for reliability and empathy. Finally, it was proposed to managers practices that can be applied to improve the company's services.
Monografia
Keywords: Qualidade; Servqual; Industria de tintas; Quality; Servqual; Paint industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO